Legal Analysis of Domestic Violence Based on the Mazhab Syafi’i and Indonesian Positive Law - Muhammad Riezky Pradana Mukhtar; AlMubarok, Misbakhul Munir; Budiman Mustofa (JUSTISI, 2025)
This research aims to examine how standards for handling domestic violence can be formed by considering the views of the Shafi'i Mazhab and positive law in Indonesia. The method of research used is normative legal research using the statutory approach method and conceptual approach method. The novelty in this research compared to previous research lies in the dual approach used in analyzing cases of domestic violence, namely through the perspective of the Shafi'i Mazhab and Indonesian positive law. The results show that both Indonesian positive law and the Shafi'i Mazhab consider domestic violence as an act that is contrary to the principles of justice and welfare in the family. However, there are differences in their perspective and legal implementation. The conclusion in Syafi'i's view, domestic violence is associated with the concept of nusyûz, which allows husbands to discipline their wives within strict limits, but this approach is no longer considered relevant in the modern era that rejects all forms of physical violence. Meanwhile, Law No. 23/2004 on the Elimination of Domestic Violence provides comprehensive protection against various forms of domestic violence, although it still faces implementation challenges such as weak law enforcement, patriarchal culture, and social stigma. Therefore, a renewal of the understanding of Islamic law is needed.